Dampak amaliyatu tadris terhadap kompetensi profesional alumni Pondok Modern Darussalam Gontor Kampus 4 - Firdaus, Rangga; Thoifah, Ianatut; Yusuf, Muhammad (TA`DIBUNA, 2024)
This study aims to analyze the impact of implementing the amaliyatu tadris program on alumni of Pondok Modern Darussalam Gontor (PMDG) campus 4. This is based on PMDG's ability to maintain an effective teaching system for over 90 years by relying on alumni as educators without recruiting teachers from external parties. This study aims to see the impact of amaliyatu tadris on the professional competence of PMDG campus 4 alumni, as well as to understand the contribution of amaliyatu tadris to the sustainability and success of PMDG in maintaining the quality of education. The method used in this research is qualitative, with a case study approach that is expected to describe the data in accordance with the research focus to achieve the predetermined objectives. The amaliyatu tadris program has been proven to improve the professional teaching competencies of PMDG campus 4 alumni, including the ability to make teaching preparations, apply effective teaching methods, and master the material. This is reinforced by the tanqihu-l-i'dad and naqdu tadris systems that maintain the quality standards of teaching at PMDG campus 4. The program provides not only theoretical knowledge but also in-depth practical experience, ensuring graduates can face educational challenges well. AbstrakPenelitian ini bertujuan untuk menganalisis dampak pelaksanaan program amaliyatu tadris terhadap kompetensi profesional alumni Pondok Modern Darussalam Gontor (PMDG) kampus 4. Serta memahami kontribusi amaliyatu tadris terhadap keberlangsungan dan keberhasilan PMDG dalam mempertahankan kualitas pendidikan. Hal tersebut didasari oleh kemampuan PMDG dalam mempertahankan sistem pengajaran yang efektif selama lebih dari 90 tahun dengan mengandalkan alumni sebagai tenaga pendidik tanpa melakukan perekrutan dari pihak eksternal. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan studi kasus dengan harapan dapat menggambarkan data sesuai dengan fokus penelitian guna mencapai tujuan yang ditetapkan. Program amaliyatu tadris terbukti meningkatkan kompetensi profesional alumni PMDG kampus 4, termasuk kemampuan membuat persiapan mengajar, menerapkan metode pengajaran yang efektif, dan menguasai materi. Hal ini diperkuat oleh sistem tanqihu-l-i’dad dan naqdu tadris yang menjaga kualitas pengajaran di PMDG kampus 4. Selain memberikan pengetahuan teoritis, program ini juga memberikan pengalaman praktis, memastikan alumninya mampu menghadapi tantangan pendidikan dengan baik.